Chromosome aberrations in human soft-tissue tumors and their diagnostic and prognostic significance - Limon, Janusz (Contemporary Oncology/Współczesna Onkologia, 2001)
Cytogenetic studies of soft tissue sarcomas have revealed that several benign and malignant soft tissue sarcomas have displayed highly specific chromosome aberrations. The primary aberrations are unique for the particular tumor type and consequently aid in differential diagnosis of these tumors. Such specific reciprocal translocations include: t(11;22) (q24;q12) in Ewing sarcoma and peripheral primitive neuroepithelial tumors, t(X;18)(p11;q11) in synovial sarcoma, t(12;16)(q13;p11) in myxoid and round cell liposarcoma, t(2;13)(q35;q14) in alveolar rhabdomyosarcoma, and t(12;22) (q13;q22) in clear cell sarcoma of tendons and aponeuroses. Molecular studies have indicated that some sarcoma-specific translocations result in the gene fusion which can be detected in the tumor even in the paraffin embedded tissue. The correlation between of chromosome changes in the tumor cells with survival or risk of recurrence have to be studied in more detail and throughly evaluated.